Unsuccessful lists of the Kurdistan Regional Parliamentary Elections between the first and fourth rounds: A study in political geography - كريم, احمد رفيق (Sulaimani Journal for Humanities, 2025)
During the present investigation, four rounds of Kurdistan parliament elections are performed, more than half of the lists of the conflicted lists were not capable of sending any candidate to the parliament. Therefore, in this paper the number of lists, their falied votes and the ratio of votes lost in the elections on the level of Kurdistan regional government and management units would be investigated and analysed by using analytic and comparative methods and tools. Weak electing plans of these lists, weak election power and the lack of any political parties ( of most of them), weak candidates, the illegal mechanisms from the side of the main Kurdistan parties for the sake of increasing the number of voters are among the factors of the disappointment and loss of these lists in Kurdistan parliament elections.